Factors Affecting Visiting Post Integrated Service for Elderly in the Work Area of Hinai Kiri Health Center, Langkat Regency - Sudomo Colombus Situmorang; Asriwati Asriwati; Mey Elisa Safitri (Journal La Medihealtico, 2022)
The purpose of this study was to analyze the factors that influence the visit of the posyandu for the elderly in the Hinai Kiri Health Center Work Area, Langkat Regency. This study uses a quantitative method with a cross sectional design, with a sample of 59 respondents. This research uses a questionnaire. The research time is March-November 2021 as a follow-up to the end of the research. The analysis of this study used Univariate, Bivariate and Multivariate. The statistical test used is the chi square test and longistic regression. The results of the study on the effect of Knowledge (P-value 0.008), Attitude (P-value 0.002), Distance (P-value 0.004), Family Support (P-value 0.009), Health Officer Support (P-value 0.003), and based on the test logistic regression Knowledge, Distance, Attitude, Family Support, Support of Health Workers are variables that affect Posyandu visits. The conclusion in this study shows that there is a significant influence between knowledge, attitude, distance, family support and support from health workers on posyandu visits in the Hinai Kiri Health Center Work Area, Secanggang District, Langkat Regency. It is recommended to health workers at the Puskesmas in particular to improve counseling and counseling more intensively about the importance of the posyandu for the elderly on a regular basis and to motivate the elderly to be more routine to participate in elderly visits at least once a month so that the health condition of the elderly is maintained.